2008
DOI: 10.1021/jm801042a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Benzothiazole-Based Analogues as Novel, Potent, and Selective Fatty Acid Amide Hydrolase Inhibitors

Abstract: High-throughput screening (HTS) identified benzothiazole analogue 3 as a potent fatty acid amide hydrolase (FAAH) inhibitor. Structure-activity relationship (SAR) studies indicated that the sulfonyl group, the piperidine ring and benzothiazole were the key components to their activity, with 16j being the most potent analogue in this series. Time-dependent preincubation study of compound 3 was consistent with it being a reversible inhibitor. Activity-based protein-profiling (ABPP) evaluation of 3 in rat tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 40 publications
(82 reference statements)
5
85
2
Order By: Relevance
“…117 The determination of selectivity by ABPP indicated that compound 87 exerted no off-target activity against numerous enzymes (such as TGH, KIAA1363, and carboxy esterases). 117 A series of non-covalent and reversible FAAH inhibitors was disclosed by Amgen in 2011. 118 Typically, compound 88 ( Figure 36) exerted potent capacity to disable FAAH-mediated hydrolysis.…”
Section: Other Faah Inhibitorsmentioning
confidence: 99%
“…117 The determination of selectivity by ABPP indicated that compound 87 exerted no off-target activity against numerous enzymes (such as TGH, KIAA1363, and carboxy esterases). 117 A series of non-covalent and reversible FAAH inhibitors was disclosed by Amgen in 2011. 118 Typically, compound 88 ( Figure 36) exerted potent capacity to disable FAAH-mediated hydrolysis.…”
Section: Other Faah Inhibitorsmentioning
confidence: 99%
“…30 Urea derivatives as prepared by Pfizer, Takeda, and us operate via a similar mechanism but have aromatic amines as leaving groups rather than alcohols or phenols. 31 40 Amgen, 41 Renovis, 42 and Johnson and Johnson. 43 Several compounds have been profiled to some degree in the clinic.…”
Section: T He Fatty Acid Amide Hydrolases (Faah and Faah-2)mentioning
confidence: 99%
“…Inhibition by N-alkylcarbamates is based on irreversible acylation of the active site serine [25]. Recently reported other structure families with inhibitory activity against FAAH include (thio)hydantoins [26], piperidine-and piperazine ureas [27,28], sulfonyl derivatives [29] and boronic acid derivatives [30].…”
Section: Introductionmentioning
confidence: 99%